2024
DOI: 10.3390/plants13030392
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis of Leaf Chlorophyll Content in Aquaponically Grown Lettuce Using Hyperspectral Reflectance and RGB Images

Mohamed Farag Taha,
Hanping Mao,
Yafei Wang
et al.

Abstract: Chlorophyll content reflects plants’ photosynthetic capacity, growth stage, and nitrogen status and is, therefore, of significant importance in precision agriculture. This study aims to develop a spectral and color vegetation indices-based model to estimate the chlorophyll content in aquaponically grown lettuce. A completely open-source automated machine learning (AutoML) framework (EvalML) was employed to develop the prediction models. The performance of AutoML along with four other standard machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Wood et al [47] observed that the RGB indices enabled the estimation of the a, b, and total chlorophyll concentrations of microalgal cultures in situ. Taha et al [48] demonstrated the feasibility of using RGB indices to estimate the chlorophyll content of lettuce. In this study, the correlations between 28 RGB indices derived from digital camera images and the anthocyanin content were strong, indicating that these indices were suitable for establishing predictive models of the anthocyanin content.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al [47] observed that the RGB indices enabled the estimation of the a, b, and total chlorophyll concentrations of microalgal cultures in situ. Taha et al [48] demonstrated the feasibility of using RGB indices to estimate the chlorophyll content of lettuce. In this study, the correlations between 28 RGB indices derived from digital camera images and the anthocyanin content were strong, indicating that these indices were suitable for establishing predictive models of the anthocyanin content.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in green hues due to foliar nitrogen (N) content can result in class separation in an RGB image bank when it comes to computer vision. Thus, this pigment becomes essential in the context of precision agriculture because it serves as a basis for quantifying foliar N content [4][5][6]. A practical and quick way to determine the existence of nutrient deficiency in plants is through visual diagnosis.…”
Section: Introductionmentioning
confidence: 99%